Dengue and Other Arbovirus Infections among Schoolchildren, Haiti, 2021 - Rigan Louis; Tracey L. Moquin; Carla Mavian; Assonic Barthelemy; Ruiyu Pu; Benjamin Anderson; V. Madsen Beau De Rochars; Maureen T. Long; Marco Salemi; John A. Lednicky; J. Glenn Morris (Emerging Infectious Diseases, 2025)
In 2021, we screened 91 children in Haiti with acute undifferentiated febrile illness for arbovirus infections. We identified a major outbreak of dengue virus type 2, with 67% of the children testing positive. Two others were positive for chikungunya East/Central/South African IIa subclade, and 2 were positive for Zika virus.